2019
DOI: 10.1080/13813455.2018.1563189
|View full text |Cite
|
Sign up to set email alerts
|

Eight sessions of endurance training decrease fasting glucose and improve glucose tolerance in middle-aged overweight males

Abstract: Exercise improves metabolic regulation and reduces the risk for developing type 2 diabetes and other metabolic diseases. The recommendations for exercise are rather general and the health benefits of controlled training studies are important to make better recommendations. In the present study, we report that eight endurance training sessions over three weeks reduced fasting glucose, and improved glucose tolerance and plasma lipids in sedentary middle-aged males (44-64 years) with overweight or obesity (BMI 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 56 publications
(65 reference statements)
2
13
0
Order By: Relevance
“…In exercise interventions, standardized work is normally performed at a specific workload or intensity for a given duration. For instance, in a study performed by our research group, aerobic training sessions involving ∼40 min of cycling at high intensity (75% VO 2max ) resulted in an energy expenditure of 600 kcal for untrained, lean, middle-aged males (Jelstad et al, 2019). Three weekly sessions each with a 600 kcal expenditure (a total of 1,800 kcal per week) correspond to the energy in 234 g of fat and 12 weeks of training intervention with such energy expenditure corresponds to the energy in 2.8 kg of fat.…”
Section: Exercise and Metabolic Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…In exercise interventions, standardized work is normally performed at a specific workload or intensity for a given duration. For instance, in a study performed by our research group, aerobic training sessions involving ∼40 min of cycling at high intensity (75% VO 2max ) resulted in an energy expenditure of 600 kcal for untrained, lean, middle-aged males (Jelstad et al, 2019). Three weekly sessions each with a 600 kcal expenditure (a total of 1,800 kcal per week) correspond to the energy in 234 g of fat and 12 weeks of training intervention with such energy expenditure corresponds to the energy in 2.8 kg of fat.…”
Section: Exercise and Metabolic Regulationmentioning
confidence: 99%
“…Members of our group often examine well-trained, lean young males with a VO 2max of 50-75 mL/(kg•min −1 ) (Rustad et al, 2016;Sollie et al, 2018); in contrast, the VO 2max for untrained middle-aged males is approximately 45 mL/(kg•min −1 ) (Langleite et al, 2016;Jelstad et al, 2019). Obese people have reduced cardiorespiratory fitness and their VO 2max may be reduced to 20 mL/(kg•min −1 ) or less (Christ-Roberts et al, 2004;Vind et al, 2011); however, this is not necessarily solely due to low cardiorespiratory fitness but may also result from an increase in body weight.…”
Section: Energy Expenditure During Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…Exercise has profound effects on metabolism and previous research has shown that an acute bout of endurance exercise results in a transient increase in insulin sensitivity and glucose tolerance (Mikines et al, 1988;Annuzzi et al, 1991;Brestoff et al, 2009;Jensen et al, 2011;Cartee, 2015b;Ortega et al, 2015;Jelstad et al, 2019). Exercise prior to lipid infusion alleviates insulin resistance (Schenk and Horowitz, 2007;Pehmoller et al, 2012;Phielix et al, 2012), but less is known about the effects of exercise on glucose tolerance during an LCHF diet.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the lack of difference between-groups, we cannot conclude that inclusion of exercise in weight-loss programs will improve AUC insulin in this population. Previous studies with regular exercise for participants with overweight and obesity have shown improvements in AUC insulin (Jelstad et al, 2019;Bergman and Goodpaster, 2020). However, the positive effect of exercise on glucose disposal is essential, as the reduction of pancreatic secretion of insulin may be an important factor in preventing T2DM later on in life.…”
Section: Auc Insulinmentioning
confidence: 99%